2003
DOI: 10.1023/a:1021210805867
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The interval between the vasectomy and the sperm retrieval procedure has no effect on the outcome until the interval of 14 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Through the categorized analysis of the 27 articles that composed the final sample, we found that all were published between 2003 and 2019. Of these, 4 were cross-sectional studies ( Pasqualotto et al ., 2003 ; Esteves & Glina, 2005 ; Cota et al ., 2012 ; Souza et al ., 2017 ), 12 were cohort studies ( Pinheiro et al ., 2003 ; Borges et al ., 2003 ; Glina et al ., 2005 ; Pasqualotto et al ., 2005 ; Romão et al ., 2010 ; Semião-Francisco et al ., 2010 ; Cota et al ., 2012 ; Borges et al ., 2013 ; Coelho Neto et al ., 2015 ; Maia-Filho et al ., 2015 ; Scheffer et al ., 2017 ; Bercaire et al ., 2018 ); 6 were case-control studies ( Setti et al ., 2011 ; Pasqualotto et al ., 2012 ; Cavagna et al ., 2012 ; Picinato et al ., 2014 ; Donabela et al ., 2015 ; Costa et al ., 2016 ); 3 were case reports ( Valle et al ., 2012 ; Taitson et al ., 2012 ; Borges et al ., 2016 ) and 2 were randomized controlled trials ( Geber & Sampaio, 2013 ; Nastri et al ., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the categorized analysis of the 27 articles that composed the final sample, we found that all were published between 2003 and 2019. Of these, 4 were cross-sectional studies ( Pasqualotto et al ., 2003 ; Esteves & Glina, 2005 ; Cota et al ., 2012 ; Souza et al ., 2017 ), 12 were cohort studies ( Pinheiro et al ., 2003 ; Borges et al ., 2003 ; Glina et al ., 2005 ; Pasqualotto et al ., 2005 ; Romão et al ., 2010 ; Semião-Francisco et al ., 2010 ; Cota et al ., 2012 ; Borges et al ., 2013 ; Coelho Neto et al ., 2015 ; Maia-Filho et al ., 2015 ; Scheffer et al ., 2017 ; Bercaire et al ., 2018 ); 6 were case-control studies ( Setti et al ., 2011 ; Pasqualotto et al ., 2012 ; Cavagna et al ., 2012 ; Picinato et al ., 2014 ; Donabela et al ., 2015 ; Costa et al ., 2016 ); 3 were case reports ( Valle et al ., 2012 ; Taitson et al ., 2012 ; Borges et al ., 2016 ) and 2 were randomized controlled trials ( Geber & Sampaio, 2013 ; Nastri et al ., 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the assisted reproduction techniques, 7 studies (25.92%) mentioned that patients were submitted to intracytoplasmic sperm injection (ICSI) or conventional in vitro fertilization (IVF) ( Cota et al ., 2012 ; Geber & Sampaio, 2013 ; Coelho Neto et al ., 2015 ; 2016 ; Costa et al ., 2016 ; Souza et al ., 2017 ; Bercaire et al ., 2018 ); 18 studies (66.66%) cited ICSI exclusively ( Pinheiro et al ., 2003 ; Borges et al ., 2003 ; Pasqualotto et al ., 2003 ; Glina et al ., 2005 ; Esteves & Glina, 2005 ; Pasqualotto et al ., 2005 ; Romão et al ., 2010 ; Semião-Francisco et al ., 2010 ; Setti et al ., 2011 ; Pasqualotto, et al ., 2012 ; Valle et al ., 2012 ; Taitson et al ., 2012 ; Nastri et al ., 2013 ; Picinato et al ., 2014 ; Maia-Filho et al ., 2015 ; Donabela et al ., 2015 ; Borges et al ., 2016 ; Scheffer et al ., 2017 ); and 2 studies (7.40%) cited the Intracytoplasmic Injection of Morphologically Selected Sperm (IMSI) ( Cavagna et al ., 2012 ; Borges et al ., 2013 ). IVF was used mainly in cases associated with female infertility, such as endometriosis, poor ovarian response, polycystic ovary syndrome and advanced age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported a case in which a twin a pregnancy was achieved with PESA/TESA and ICSI in a couple after 25 years of obstructive interval. Previous studies have demonstrated that the obstructive interval negatively influences pregnancy (Abdelmassih et al, 2002;Borges Júnior et al, 2003), ongoing pregnancy (Abdelmassih et al, 2002;Borges Júnior et al, 2003), implantation (Abdelmassih et al, 2002;Borges Júnior et al, 2003) and miscarriage (Borges Júnior et al, 2003) rates. One study, with severe limited power, failed to demonstrate such associations (Sukcharoen et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…The influence of the obstructive interval (time elapsed since vasectomy) on the outcomes of ICSI with SSR has been addressed in some studies with conflicting results (Sukcharoen et al, 2000;Abdelmassih et al, 2002;Borges Júnior et al, 2003). This case report will describe a successful twin pregnancy obtained after 25 years of obstructive interval.…”
Section: Introductionmentioning
confidence: 98%